(untitled) (Contemporary Mathematics, 2025)
A public-key cryptosystem using orthogonal product states is presented. It is based on the non-locality of some orthogonal product states in an untangled two-particle quantum system. Every user creates a group of two-particle quantum systems and shares them with a key management center (KMC) in which the first particle of the two-particle systems are held by the user and the second particle of the two-particle systems are held by KMC. This is the user’s (private key, public key) pair. Two users can exchange secret message by this cryptosystem. The laws of quantum physics guarantees that this cryptosystem has unconditional security. There are no entangled states needed in this public-key cryptosystem. Moreover both users and KMC needn’t perform complex quantum operations except quantum measurements on a particle or a two-particle system. So the public-key cryptosystem is feasible to implement by today’s technology. One orthogonal product quantum system contributes three bits to the key. So the cryptosystem has a high channel capacity.